1996
DOI: 10.1159/000117216
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Characterized by Abundant Neurofibrillary Tangles and Scarce Senile Plaques: A Quantitative Pathological Study

Abstract: We report an elderly case who had demonstrated progressive memory disturbance and disorientation for 4 years. The clinical features were indistinguishable from late-onset dementia of the Alzheimer type (DAT). Neuropathologically, however, senile plaques (SPs) were almost absent throughout the brain. In contrast, numerous neurofibrillary tangles (NFTs) were observed in the hippocampus and neighboring regions, with much higher density than age-mateched normal controls. The immunohistochemical and ultrastructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…A subset of patients with PART (previously referred to as SD-NFT, TPSD, etc.) display marked clinical impairment in the absence of any other recognizable substrate for dementia [14, 21, 39, 60, 66, 72, 99, 142]. The average age of death is generally higher for these patients than those with AD pathology [37, 79, 107].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of patients with PART (previously referred to as SD-NFT, TPSD, etc.) display marked clinical impairment in the absence of any other recognizable substrate for dementia [14, 21, 39, 60, 66, 72, 99, 142]. The average age of death is generally higher for these patients than those with AD pathology [37, 79, 107].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Patients with mild-to-moderate AD-type neurofibrillary degeneration in the medial temporal lobe, but lacking Aβ plaques, have been described in European, Japanese, North and South American cohorts [2, 3, 14, 51, 52, 58, 69, 72, 79, 81, 82, 126, 142, 147, 149, 151]. NFT are practically universal in older persons' brains [22, 30, 108, 132], and are also observed in a more limited distribution in many younger individuals [30, 32, 42].…”
Section: Introductionmentioning
confidence: 99%
“…Outside the collateral sulcus, the AD pa- tients presented with abundant NFTs in the lateral occipitotemporal gyrus and inferior temporal gyrus compared with SD-NFT. The NFTs in SD-NFT were labelled by the antibodies to tau [phosphorylation-dependent (AT8, AT100, AT180, and AT270) and independent (TAU-2 and anti-human tau)], PHF, and ubiquitin as found in AD [9] (fig. 4).…”
Section: Neuropathologic Findingsmentioning
confidence: 99%
“…We studied demented elderly patients with such neuropathologic features [9,10], and compared them with agematched AD patients in clinicopathologic and genetic aspects [10]; our results indicated that this neuropathologic condition would represent a disease entity different from AD [10]. Therefore, we have proposed the term, 'senile dementia of the NFT type' (SD-NFT), which is distinguished from late-onset AD, i.e., senile dementia of the Alzheimer type [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, all cases with neuritic plaques have neuropil threads and neurofibrillary tangles both in the entorhinal region and amygdala, indicating that neuropil threads and neurofibrillary tangles might be a prerequisite for the development of neuritic plaques (table 1). Recent reports on a rare form of senile dementia of the Alzheimer type characterized by the absence or near absence of senile plaques [Ulrich et al, 1992;Bancher and Jellinger, 1994;Itoh et al, 1996], as some cases at limbic stages, show (table 1, neurofibrillary stages III-IV) that even an advanced neurofibrillary pathology may remain devoid of neuritic plaques ( fig.¤1).…”
Section: Discussionmentioning
confidence: 99%